Clinical and Radiological Characteristics of a Patient with a Pituitary Tumor of the Prolactinoma Type — Case Report - Anna Krzentowska; Maria Smoter (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Prolactinoma is a benign tumor of the anterior lobe of the pituitary gland. It is the most common type of pituitary adenoma. In terms of size, micro- and macroprolactinomas are distinguished. Prolactinoma is mostly a benign tumor (>98%). Symptoms in hyperprolactinemia are the result of excess hormone and mass effect. Symptoms of the mass effect include headaches, visual disturbances and dizziness. Excess prolactin leads to infertility and “amenorrhea — galactorrhea” syndrome.